Effectiveness of laparoendoscopic surgical treatment with single-site / single-incision laparoscopic surgery method in gynecological practice - Ilaha Ariz Guliyeva (Zaporožskij Medicinskij Žurnal)
Laparoendoscopic single-site surgery (LESS) / single-incision laparoscopic surgery (SILS) is considered the effective minimally invasive laparoendoscopic method for solving gynecological problems.